Food And Feeding Habits of Upeneus Vittatus (Forsskal, 1775) (Yellowstriped Goatfish) from South East Waters of India - Harshavardhan D. Joshi; A. Tiburtius; J. C. Dhas; C. Babu; Karankumar K. Ramteke; Upasana Sahoo; Y. Tharumar (Journal of Indian Fisheries Association, 2018)
Facet of food and feeding habitats of Upeneus vittatus, collected from Motor Fishing Vessel (M.F.V.) Samudrika and Kasimedu fishing harbour, Chennai, are reported in this paper. Analysis of gut content of the total of 2,354 specimens, ranging from 110 to 240mm in total length, revealed that the species feeds mainly on Acetes spp (24.98 %), other shrimps (13.58 %), crabs (14.30 %), worms (9.69 %], teleost (12.74 %), bivalves (4.53 %] and the remaining (20.15 %) consisted of digested food items. Frequency of occurrence of teleost fishes was observed in specimen with Total Length more than 172mm. Acetes spp ranked first amongst all crustaceans throughout the year. The present study on the feeding habits reveals that this species has high preference for crustaceans and can be labelled as benthic feeders.